The influence of audit quality, company size, profitability, and inventory intensity on tax avoidance in manufacturing companies registered on the IDX in 2020-2022 - Sagala, Yos Hengky Olbioctavian; Pangaribuan, Hisar; Siagian, Harlyn L. (Institute of Computer Science (IOCS), 2024)
In the era of globalization, corporate financial management has become increasingly complex. Effective financial management, particularly in tax planning, is crucial for addressing the rapidly changing market dynamics. Taxes, as a major cost component, require a strategic and measured approach. Good tax management not only optimizes tax liabilities but also positively impacts the financial performance of the company. This research aims to analyze the influence of audit quality, company size, profitability, and inventory intensity on tax avoidance practices in manufacturing companies listed on the Indonesia Stock Exchange during the period 2020-2022. The research utilizes a descriptive approach with quantitative methods. Secondary data from the annual financial reports of manufacturing companies are used. Samples are selected through purposive sampling techniques. The analysis results show that approximately 13.8% of the variation in tax avoidance practices is influenced by the examined independent variables. Other factors account for the remaining 86.2%. Based on the findings, it can be concluded that audit quality, company size, profitability, and inventory intensity have an influence on tax avoidance practices. Effective tax management can help companies improve financial performance and strengthen overall tax compliance